Use of Preoperative High-Resolution Ultrasound System to Facilitate Elevation of the Superficial Circumflex Iliac Artery Perforator Flap - Yoshimatsu, Hidehiko; Karakawa, Ryo; Fuse, Yuma; Okada, Akira; Hayashi, Akitatsu; Yano, Tomoyuki (Journal of Reconstructive Microsurgery, 2021)
Background During elevation of the superficial circumflex iliac artery (SCIA) perforator (SCIP) flaps, the flap pedicle must often be converted from the superficial branch to the deep branch of the SCIA, complicating and prolonging the procedure. The goal of the present study was to demonstrate the effectiveness of high-resolution ultrasonography to decrease the conversion rate on which no previous report has focused, by making a comparison with a conventional method.Methods Forty-five consecutive cases where free SCIP flap transfer was performed for reconstruction were retrospectively reviewed. To preoperatively mark the course of the superficial branch, handheld Doppler ultrasonography was used in 27 cases (group 1) and a high-resolution ultrasound system in 18 cases (group 2).Results The conversion rate was significantly greater in group 1 than in group 2 (10/27 [37%] vs. 0/18 [0%], p = 0.003]. The frequency of use of multiple venous anastomoses was significantly higher in group 1 than in group 2 (21/27 [78%] vs. 2/18 [11%], p < 0.001). The operative time was significantly longer in group 1 than in group 2 (p = 0.038). There were no significant differences in postoperative complication rates (1/27 [4%] versus 0/18 [0%], p = 1.0).Conclusion The use of a preoperative high-resolution ultrasound system significantly decreased the rate from of intraoperative conversion from the superficial branch to the deep branch of the SCIA. It also resulted in significantly fewer venous anastomoses and a shorter operative time, while maintaining a low incidence of postoperative complications.
Keywords: ultrasonography; superficial circumflex iliac artery perforator flap; superficial branch of the superficial circumflex iliac artery